Reporting rape: victim perspectives on advocacy support in the criminal justice process - Brooks-Hay, Oona (2017)
Concerns about the criminal justice response to rape have prompted the development of victim advocacy services across a range of jurisdictions, yet research evidence about the nature, meaning and value of advocacy remains limited. This article draws upon a study evaluating an innovative advocacy model introduced in Scotland to assist reporting rape to the police. Findings from interviews with nine victims highlight the importance of advocacy that is independent of statutory and criminal justice agencies. However, it is argued that this does not mitigate the need for specialization or reform in the criminal justice response to rape and, further, that the distinction between advocacy at an individual and societal level represents a false dichotomy